Actualization of Children's English Skills Towards Society 5.0 Era - Muhammad Nur Hasan; Jayyid Jihad Asfi Mashabi; Khoiroh Ummu Rodhiyah (Institut Agama Islam Tarbiyatut Tholabah, 2022)
Facing the Society 5.0 era, the world of education plays an important role in improving the quality of human resources. As well to education some elements and stakeholders such as the government, community organizations and the whole community also participated in welcoming the coming Society 5.0 era. To answer the challenges of the Industrial Revolution 4.0 and Society 5.0 in the world of education required life skills of the 21st century or better known as 4C (Creativity, Critical Thinking, Communication, and Collaboration). This research method using questionnaire survey by asking several questions to the respondents and doing direct observation at the research site. The total number of them was 12 with details 7 teachers and 5 parents of students respectively. The results of the study show that the majority of respondents agree that it is very important to hone children's English skills for preparing the challenges in the Society 5.0 era. Where the times are getting more advanced and global competition is a necessity. Self-preparation through English language skills started from the education is a solution today. So that children have no difficulty to adapt in the modern or digital world and it is hard to be competitive looking for job vacancies in the future. Consequently, children are expected be technologically literate and fluent English in Society 5.0, considering that English has been established as an international language, business language, and technology language.